Nanoindentation: Introduction and applications of a non-destructive analysis - Zaid H. Mahmoud; H.N.K. AL-Salman; Ehsan Kianfar (Nano TransMed)
Nanoindentation test is known as a powerful method for non-destructive characterization and analysis of mechanical properties of nanoscale materials. In this method, the indenting tip penetrates the surface of the sample by applying a force of several millinewtons to the extent of several nanometers, and the resulting force-displacement curve is used as the output of the test to calculate the mechanical characteristics of the sample, including hardness and elastic modulus, as well as to identify various mechanical phenomena such as Creep, strain hardening, surface cracking, phase transformations, creep and fracture toughness of the material are used. In this article, the Nanoindentation method is briefly introduced and its principles and basics are discussed. The application of this method is valid for analyzing the mechanical properties of a wide range of materials. The purpose of this article is to familiarize researchers and experts in engineering fields with the nanoindentation method as a non-destructive analysis and its effective use in their respective fields of application.